Cities as implements or facilities – The need for a spatial morphology in smart city systems. Issue 2 (March 2017) - Marcus, Lars; Koch, Daniel
In light of the urgent threats presented by climate change and rapid urbanisation, interest in 'smart city systems' is mounting. In contrast to scholarship that poses 'smartness' as something that needs to be added to cities, recent developments in spatial morphology research pursue a view of the built fabric of cities as an extension of the cognitive human apparatus, as well as a material formulation of social, cultural and economic relations and processes. The built fabric of cities needs to be understood as a highly intelligent artefact in itself, rather than simple, dead matter. The current focus on high-tech systems risks concealing the fact that the machine is already there . In contrast to the technological 'implements' of smart city systems, this article looks at cities as 'facilities' – that is, as technologies that slow down, store and maintain energy as a resource for a variety of purposes. The article builds on space syntax research in order to give precision to the understanding of the affordances the cities offer their various processes and the ways in which cities operate as information storage and retrieval devices for individuals and for society. The city must be considered, we argue, in terms of a range of tangled, interdependent systems, reaching from individual buildings to the whole city, an understanding anchored in notions of 'diversity' and 'density' (recently gathered under the concept of 'spatial capital') and in research addressing how the distribution of space and artefacts serve as means of knowledge communication (specifically, in complex buildings such as libraries and department stores). In conclusion, we argue that existing discussions on 'smart city systems' would benefit acknowledgement of the role of cities as facilities.